1975
DOI: 10.1136/thx.30.5.543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atropine on sputum production.

Abstract: (1975). Thorax, 30,[543][544][545][546][547]. Efect of atropine on sputum production. The effect of atropine on sputum production has been studied in patients with asthma, chronic bronchitis, and bronchiectasis in some of Wvhom there was bronchorrhoea. In three patients a reduction in sputum volume was observed after atropine but it would seem that the decrease was mainly due to the inhibitory effect on salivary secretion which facilitates spitting. The one patient treated with long-term oral atropine showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the oxitropium group the elasticity (G') of the sputum increased from 68 (12) dyne/cm2 on day 0 to 97 (20) dyne/cm2 after eight weeks (p < 0 05, n = 17). The dynamic viscosity (i') also tended to increase from 32 (14) to 40 (22) poise, but this was not significant.…”
Section: Resultsmentioning
confidence: 94%
“…In the oxitropium group the elasticity (G') of the sputum increased from 68 (12) dyne/cm2 on day 0 to 97 (20) dyne/cm2 after eight weeks (p < 0 05, n = 17). The dynamic viscosity (i') also tended to increase from 32 (14) to 40 (22) poise, but this was not significant.…”
Section: Resultsmentioning
confidence: 94%
“…Atropine alone, however, had no effect on the release of mucus [27]. L opez ‐V idriero et al [35] found that atropine had an inhibitory effect on bronchial gland secretion in three patients (with a diagnosis of chronic bronchitis, intrinsic asthma or bronchiectasis in combination with bronchorrhoea). The single administration of atropine (either by inhalation or intramuscular injection) is reported not to alter sputum viscosity in patients with chronic bronchitis, asthma or bronchiectasis [35, 36].…”
Section: Anticholinergicsmentioning
confidence: 99%
“…Because human airway epithelium is likely to be primarily absorptive (5,22,26,62,63), a major fraction of the airway fluid seems to be derived from the submucosal gland (2,48) and follows an active Cl Ϫ secretion from the glandular acini (11,14,48). The airway secretion appears to be under tonic regulation by cholinergic nerves because oral administration of atropine reduces the secretion (35) and vagal cooling reduces it by ϳ40% (59). An in vivo observation indicated that cholinergic agents were much more potent stim-ulators of gland secretion than were adrenergic agonists when estimated using hillock formations of a powdered tantalum layer coating the airway surface (43).…”
mentioning
confidence: 99%